2015
DOI: 10.1007/s13202-014-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of proppant agglomeration during settling in hydraulic fractures

Abstract: The micromechanics of proppant settling in quiescent fluid in a rough and relatively narrow rock fracture is investigated. The study focuses on particleparticle and particle-wall interactions in a dense-phase particle settling. The study used a coupled discrete element method and computational fluid dynamics (DEM-CFD) code because DEM-CFD is the most suitable computational method for modeling the frequent interactions of dense assembly of rigid particles and enables modeling of two-way solid-fluid interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Unfortunately, the final distributions of proppant grains are virtually impossible to image nowadays, and direct numerical simulations of suspension flows in narrow apertures have just begun to emerge (Shiozawa & McClure, 2016;Tomac & Gutierrez, 2015). In general, the processes of proppant transport and settlement are complex and dependent on a large number of parameters including proppant density, fracking fluid properties, pumping rate, and fracture geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the final distributions of proppant grains are virtually impossible to image nowadays, and direct numerical simulations of suspension flows in narrow apertures have just begun to emerge (Shiozawa & McClure, 2016;Tomac & Gutierrez, 2015). In general, the processes of proppant transport and settlement are complex and dependent on a large number of parameters including proppant density, fracking fluid properties, pumping rate, and fracture geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the fact that dispersivity has a stronger effect on SW tracer signals than the other parameters, in conjunction with relatively narrow ranges for parameters like proppant-packing porosity, GPF thickness or WF aperture, may allow to at least roughly estimate dispersivity without knowing the exact values of other parameters. A possible workaround to parameter interplay is the use of semi-empirical correlations between hydrogeological parameters to constrain the value of either dispersivity as a function of fracture aperture and porosity (Horne and Rodriguez, 1981;Fossum and Horne, 1982;Pruess and Bodvarsson, 1984), or porosity as a function of permeability (Guimerà and Carrera, 1997), or proppantpacking dispersivity as a function of proppant treatment protocols (Tomac and Gutierrez, 2015). Alternatively, it may be possible to make a priori assumptions on the magnitude of the Peclet number (Pe) of the overall transport scenario (with Pe defined as the ratio between tracer-invaded fracture radius and longitudinal dispersivity).…”
Section: Parameter Interplay and Numerical Simulationsmentioning
confidence: 99%
“…Considerable research based on numerical simulation methods has been conducted. The numerical simulations can be divided into several types, such as the particle quasi‐fluid method, CFD‐DEM method (including LBM‐DEM, LES‐DEM, and DNS‐IB), particle tracking method, and Brownian dynamics simulation . The existing studies demonstrated that the numerical simulation is an effective means to study the particulate suspensions transport and permeability damage to the porous media.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations can be divided into several types, such as the particle quasi-fluid method, CFD-DEM method (including LBM-DEM, LES-DEM, and DNS-IB), particle tracking method, and Brownian dynamics simulation. [12][13][14][15][16][17][18] The existing studies demonstrated that the numerical simulation is an effective means to study the particulate suspensions transport and permeability damage to the porous media. The particle size-exclusion mechanism in a smooth fracture with a constrict has been extensively studied, and the general conclusion of these studies is that mechanical bridging is more prone to occur when the particle size is larger than one-third of the fracture width.…”
Section: Introductionmentioning
confidence: 99%